Analisis User Experience pada Aplikasi Diary Sumsel menggunakan Metode Heuristic Evaluation - Nuryadi, Muhammad; Rasmila, Rasmila (Universitas Nusa Cendana, 2024)
The application is a mobile application that has great potential to help users record and manage their daily notes. However, a good user experience (UX) is critical in ensuring the success and acceptance of the application. This research aims to carry out UX analysis on the application using the Heuristic Evaluation method. The Heuristic Evaluation method is used to identify potential UX problems by comparing the application with a set of pre-established design principles (heuristics). The research results show a number of findings related to the navigation, consistency, responsiveness and accessibility aspects of the Diary Sumsel application. The results of this research found a low level of improvement analysis after tracing it according to the evaluation that had been carried out. Then UX from the results of this analysis is more than enough to make users feel comfortable in becoming a membership or user list of the Diary Sumsel application in terms of several features that can be utilized in it. This research makes an important contribution in understanding and improving the UX of the Diary Sumsel application, which in turn can increase the acceptability and value of this application for users. By improving the UX, it is hoped that this application can provide greater benefits and better meet user needs.